EKSPEKTASI INFLASI DI ERA REZIM COVID-19 - R C Maulani (Jurnal Pendidikan Ekonomi Indonesia, 2022)
The purpose of this study is to explore the role of the Covid-19 pandemic event in inflation expectations and its volatility through Indonesia's inflation exchange rate. The findings document that inflation expectations and their volatility are positively affected by the Covid-19 pandemic. These results have real activity implications, while close monitoring of inflation expectations could signal inflation expectations are relinquishing risk.